From Awareness to Action: Mindfulness Brief Interventions Shaping Positive Affect and Decision Certainty - Yani Duan; Nor Akmar Bt. Nordin; Siti Aisyah Panatik; Huayi Liu (Ital Publication, 2026)
Purpose: This study aims to explore the effect of a five-minute mindfulness audio intervention on improving state positive emotion and decision-making effectiveness under uncertainty, and to examine whether trait maximization moderates these effects among Chinese university students. Method: A randomized between-subjects experiment (N = 320) was conducted, in which participants were assigned to either a brief mindfulness exercise or a time-matched neutral audio control. State positive emotion was measured immediately after the manipulation using the PANAS positive affect scale. Participants then completed five worst-case scenario tasks (least-worst decision scenarios). Decision time, perceived decision difficulty, and the percentage of approach choices were recorded. Structural equation modeling was used to test mediation effects, and interaction modeling was applied to examine moderation. Findings: Participants in the mindfulness condition reported higher levels of positive emotion and demonstrated more effective decision-making patterns, characterized by faster decisions, lower perceived difficulty, and a higher proportion of approach-oriented choices. Positive emotion partially mediated the relationship between mindfulness and decision effectiveness. However, the benefits of mindfulness on approach choices were reduced among individuals with higher maximization tendencies. Originality/Implications: This study contributes to the literature on least-worst decision making by incorporating an affective mechanism and an individual difference moderator within a Chinese sample. The findings suggest that brief, scalable mindfulness interventions can support approach-oriented decision behavior under uncertainty, while also indicating that such interventions may need to be tailored for individuals with high maximization tendencies.